A Low-Power Algorithm for Baseband Feedback Used with Frequency Domain Multiplexing - Oral, T.; van Loon, D.; Hou, R.; Nieuwenhuizen, A. C. T.; den Hartog, R. H.; van Leeuwen, B.-J. (Journal of low temperature physics, 2012)
SRON is developing an electronic read-out system for an array of transition edge sensors (TES), which combines the techniques of frequency domain multiplexing (FDM) with base-band feedback (BBFB). An important part of this technique is implemented in digital electronics. This paper describes how a significant reduction of the power consumption of the digital electronics is realized by down-sampling to much lower frequencies using channelization and a poly-phase filter design adapted to BBFB.